IMPLEMENTATION OF REGULATION IN OVERCOMING WOMEN'S EXPLOITATION IN ADVERTISING IN INDONESIA - Sari, Fitri Meliya; Hanifah, Hanifah; Furqany, Syahril; Azmy, Kharul; Sazali, Hasan (ASPIKOM Jabodetabek Region, 2023)
This study aims to examine the implementation of regulation in overcoming the exploitation of women in advertising in Indonesia. Some factors that affect the effectiveness of regulations in overcoming the exploitation of women in advertising in Indonesia include public awareness, the application of law, education, and supervision. However, the implementation of regulations to address the exploitation of women in advertising in Indonesia faces several challenges, such as difficulties in supervision, limitations in sanctions, problems in education, and difficulties in changing culture. This paper uses a literature study method by analyzing various sources such as books, articles, and related documents. The results show that appropriate and effective regulation can help to promote gender equality and women's rights. Therefore, the government and media industry players must work together to ensure these regulations can be implemented properly and effectively.